Burden of laboratory-confirmed shigellosis infections in Guatemala 2007-2012: results from a population-based surveillance system - Sonia Hegde (BMC Public Health, 2019)
Abstract Background We describe the epidemiology and antimicrobial susceptibility patterns of culture-confirmed Shigella infections in facility-based surveillance sites in Guatemala. Current studies using quantitative molecular diagnostics suggest Shigella may contribute most to the global diarrheal disease burden. Since identification of Shigella requires culturing techniques using stool specimens and few laboratories in Guatemala routinely culture for this pathogen, little is known about the true burden of Shigella in Guatemala or, importantly, the antimicrobial resistance patterns. Methods Clinical, epidemiological, and laboratory data were collected on 5399 patients with acute diarrhea (≥3 loose stools in 24 h) from June 2007–August 2012. Multidrug resistance (MDR) was defined as resistance to ampicillin and trimethoprim/sulfamethoxazole. Results Five percent (261) of stool specimens yielded Shigella spp. The annual incidence of laboratory-confirmed infections ranged from 5.0 to 24.1 per 100,000 persons in Santa Rosa and 0.3 to 6.2 per 100,000 in Quetzaltenango; 58% of cases occurred in children < 5 years of age. Thirty patients were hospitalized; one patient died. Oral rehydration or intravenous solution was used to treat 72% of hospitalized and 15% of ambulatory cases. Fifty-nine percent of cases were S. flexneri and 51% of cases were MDR. Conclusions Shigella is an important cause of bacterial diarrhea in children and prevalence of MDR highlights the importance of appropriate treatment regimens. This study demonstrates that strengthening laboratory capacity in Guatemala can help determine causes which can lead to prevention of diarrheal diseases, particularly in children. Such capacity building is also critical for rapid detection and control of public health threats at their source and therefore for global health security.